2014
DOI: 10.1073/pnas.1406134111
|View full text |Cite
|
Sign up to set email alerts
|

Basis for substrate recognition and distinction by matrix metalloproteinases

Abstract: Genomic sequencing and structural genomics produced a vast amount of sequence and structural data, creating an opportunity for structure-function analysis in silico [Radivojac P, et al. (2013) Nat Methods 10(3):221-227]. Unfortunately, only a few large experimental datasets exist to serve as benchmarks for functionrelated predictions. Furthermore, currently there are no reliable means to predict the extent of functional similarity among proteins. Here, we quantify structure-function relationships among three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 68 publications
4
93
0
1
Order By: Relevance
“…Such methods include engineering deletion mutants (3), use of competitive ligands (4,5), and site-directed mutagenesis (6,7). In contrast to these techniques, substrate phage display is a highthroughput, unbiased approach to studying protease substrate specificity (8)(9)(10). In this method, a library consisting of 10 6 -10 9 independent phage clones, each expressing a unique potential substrate on its surface, is panned for multiple rounds with a protease, and the cleaved or uncleaved phages after each reaction are removed and amplified for subsequent rounds of selection.…”
mentioning
confidence: 99%
“…Such methods include engineering deletion mutants (3), use of competitive ligands (4,5), and site-directed mutagenesis (6,7). In contrast to these techniques, substrate phage display is a highthroughput, unbiased approach to studying protease substrate specificity (8)(9)(10). In this method, a library consisting of 10 6 -10 9 independent phage clones, each expressing a unique potential substrate on its surface, is panned for multiple rounds with a protease, and the cleaved or uncleaved phages after each reaction are removed and amplified for subsequent rounds of selection.…”
mentioning
confidence: 99%
“…Recently, using substrate phage display (17,18), we identified some of the cleavage preferences of the matrix metalloproteinase (MMP) family members (19). Here, we employed a high throughput multiplexed peptide-centric profiling technology involving the cleavage of 18,583 peptides by the 18 individual proteinases from the main subgroups of the MMP family (20).…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm is based on the position weight matrices (PWMs) approach. The original cleavage data were derived from the analysis of specific substrates selected from phage display libraries (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…The MMPs are a family of zinc-dependent endopeptidases responsible for degrading extracellular components (Creemers et al, 2001;Falk, 2006). Each MMP has its own substrate specificity (Ratnikov et al, 2014). Previous studies have suggested that MMPs may play a role in the development of several diseases, such as spontaneous early pregnancy failure (Nissi et al, 2013), solid and hematological malignancies (Chaudhary et al, 2013), and abdominal aortic aneurysms (Duellman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%